Crystallized glass tailored by controlled heat treatment for carbon dioxide capture under mild conditions. Issue 24 (7th November 2022) - Kim, Hyung-Ju; Yang, Hee-Chul; Lee, Keunyoung; Foster, Richard I.
Abstract : Depicted is the formation of crystallized alkaline earth oxide-containing glass adsorbents for radioactive carbon dioxide ( 14 CO2 ) sequestering and mineralization under mild operating conditions enabling long-term geological disposal of hazardous 14 C. Abstract : Described is the formation of crystallized alkaline earth oxide-containing glass adsorbents for radioactive carbon dioxide ( 14 CO2 ) sequestering and mineralization under mild operating conditions; thus enabling the long-term geological disposal of hazardous 14 C. The best performing crystallized glass adsorbents recorded a max CO2 capacity of 4.54 mmol g −1 and a carbonation reaction rate of 8.04 mmol g −1 h −1 .